02 Investigation of patient and practitioner views on improving pain management in the prehospital settings. Issue 3 (1st March 2011) - Iqbal, Mohammad; Spaight, Anne; Siriwardena, A Niroshan; Shaw, Deborah
Abstract : Background: Pre-hospital pain management is increasingly important with most patients (80%) presenting to UK ambulance services in pain. Around 20% of patients want more pain relief and 5% feel that ambulance crews do not adequately treat pain. A recent study in the East Midlands showed that 85.1% of AMI patients and 75% of fracture patients had a pain score but fewer than a quarter of patients assessed for and experiencing pain with either condition received opiates. Improving the pathway of prehospital pain management is therefore important and a key indicator of the quality of service. Objective: We gathered data on perspectives of pain management from patients, ambulance and accident and emergency (A&E) care staff in Lincolnshire. Method: Qualitative data were gathered through focus group (5) and interviews (28). Participants were purposively sampled from patients recently transported to hospital with pain, ambulance staff and A&E clinicians. Interviews were audiotaped and transcribed. Data were manipulated using MAXQDA and thematic analysis used iteratively to develop themes. Results: Themes emerging from the data included: (a) expectations and beliefs (b) assessment methods (c) drug treatment (d) non-drug treatment and (e) improvement strategies for pain. Patients and staff expected pain to be relieved in the ambulance; instances of refusal or inadequate analgesia were not uncommon. Pain was commonly assessed using a verbal pain score; clinical observation was also used which sometimes led to discordance between subjective experience and clinical assessment. Morphine, Entonox and oxygen were commonly used to treat pain. Reassurance, positioning and immobilisation were alternatives to drugs. Suggestions to improve prehospital pain management included addressing barriers, modifying the available drugs and developing a prehospital pain management protocol supported by training for staff. Conclusion: The findings will be used to develop an educational intervention for better pain assessment and management in the prehospital setting.